2014
DOI: 10.1007/s40670-014-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Teaching Laboratory Medicine in Microbiology to Undergraduate Medical Students: A Survey Study

Abstract: The teaching laboratory has long been a component of medical microbiology courses. Limited data suggest that many medical schools have eliminated their teaching laboratory for diagnostic microbiology despite support for active learning over didactic lectures and a concern that undergraduate medical student's education in the area of laboratory medicine is inadequate. A survey study of North American medical schools was conducted to determine if there is a trend towards decreasing or eliminating this teaching l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…There are some other studies which have identified shortcomings among medical students and/or nonpathology residents (1,3,14,(18)(19)(20) in some aspects of laboratory medicine such as inappropriate test ordering, incorrect interpretation (3,14), microscopic exam (3,15) and calculation of pre and post-test probabilities (3,16).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are some other studies which have identified shortcomings among medical students and/or nonpathology residents (1,3,14,(18)(19)(20) in some aspects of laboratory medicine such as inappropriate test ordering, incorrect interpretation (3,14), microscopic exam (3,15) and calculation of pre and post-test probabilities (3,16).…”
Section: Discussionmentioning
confidence: 99%
“…Information and objective data provided by clinical pathology laboratory plays an important role in nearly all aspects of clinical practice including diagnosis, treatment, management and prognosis (1)(2)(3)(4). It is believed that about 60-70% of medical decisions are based on laboratory test results (2,3,5).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations